Efektivitas Media Pembelajaran Sejarah Berbasis Aplikasi Canva Terhadap Hasil Belajar Kognitif Siswa SMK - Ridha Albarokah; Ajat Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study was to test a Canva-based history learning tool and evaluate its effectiveness in improving the cognitive learning outcomes of eleventh-grade students at SMK Negeri 1 Pangkalpinang. The ADDIE paradigm, encompassing analysis, design, development, implementation, and evaluation, was used in the study's Research and Development (R&D) methodology. A single-group pretest-posttest efficacy test design was employed within a mixed-methods approach. Purposeful sampling was used to identify 36 eleventh-grade students as participants. A response questionnaire, an expert validation sheet, and learning outcome tests in the form of a pretest and posttest were among the research tools. N-Gain was used to examine quantitative data to identify changes in student learning outcomes. According to the data, the average pretest score of 64.00 increased to 90.50 on the posttest, and the average N-Gain score was 0.67, considered moderate. According to the distribution of N-Gain categories, 50% of students fell into the high group, 44% into the middle category, and 6% into the low category. These findings indicate that history learning materials created using Canva successfully improved students' cognitive learning outcomes. The visual, structured, and interactive presentation of the materials, which helped students understand historical ideas and events more systematically, impacted this progress. This study advances the creation of digital learning resources and provides a creative way to improve the standards of history teaching in vocational schools.